2014
DOI: 10.1136/oemed-2014-102172
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and relative risk of hearing disorders in professional musicians

Abstract: BackgroundHearing disorders have been associated with occupational exposure to music. Musicians may benefit from non-amplified and low-intensity music, but may also have high risks of music-induced hearing loss.AimsTo compare the incidence of hearing loss (HL) and its subentities in professional musicians with that in the general population.MethodsWe performed a historical cohort study among insurants between 19 and 66 years who were employed subject to social insurance contributions. The study was conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 28 publications
0
32
0
16
Order By: Relevance
“…In a study on an audience of 204 individuals in a concert, almost 38% of the participants complained of hearing impairment 16) . According to a four-year cohort study conducted by Schink et al, the risk of NIHL among musicians was 3.6 times higher than that among the general population 17) . The results of our study were in line with all the above-mentioned studies and it can be concluded that professional musicians are at risk of NIHL.…”
Section: Discussionmentioning
confidence: 94%
“…In a study on an audience of 204 individuals in a concert, almost 38% of the participants complained of hearing impairment 16) . According to a four-year cohort study conducted by Schink et al, the risk of NIHL among musicians was 3.6 times higher than that among the general population 17) . The results of our study were in line with all the above-mentioned studies and it can be concluded that professional musicians are at risk of NIHL.…”
Section: Discussionmentioning
confidence: 94%
“…Vulnerable populations include military personnel, professional musicians, miners, and construction workers (McBride, 2004; Humes et al, 2005; Gordon et al, 2016; Schink et al, 2014), but everyday noise-exposure from leisure activities may also threaten cochlear integrity (e.g., Portnuff et al, 2011; Flamme et al, 2012; LePrell et al, 2012; Liberman et al, 2016). Noise-related damage to the cochlea scales with the intensity, duration, and number of acoustic overexposures (Harris, 1950; Eldredge et al, 1973; Hawkins et al, 1976; Bohne and Clark, 1982), and the perceptual consequences can range from degradations in temporal processing and speech perception (Plack et al, 2014; Bharadwaj et al, 2014; 2015) to significant impairments in sound detection.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies showed that musicians are exposed to loud music in the course of orchestral ensembles (Laitinen et al, 2003;Lee et al, 2005;MacDonald et al, 2008;O'Brien et al, 2008;Jansen et al, 2009;Qian et al, 2011;Rodrigues et al, 2013Rodrigues et al, , 2014, individual pratice (O'Brien et al, 2013), and teaching activities (Behar et al, 2004), among other professional and nonprofessional musical activities . Exposure to these high sound levels was associated with hearing loss (Juman et al, 2004;Morais et al, 2007;Jansen et al, 2009;Schink et al, 2014), and other hearingloss-related symptoms such as tinnitus, hyperacusis, and diplacusis (Morais et al, 2007;Laitinen, 2005;Laitinen et al, 2008;Jansen et al, 2009). Because musicians are reliant upon optimal functioning of their auditory system (Kähäri et al, 2003), hearing impairment adversely affects musicians' performance, resulting in difficulties in musical perception (Royster et al, 1991).…”
mentioning
confidence: 99%